Comparison of alcohol, povidone-iodine and octenidine dihydrochloride as skin disinfectants to reduce bacterial count prior to peripheral venous catheter insertions in newborn infants - Lily Rundjan; Rinawati Rohsiswatmo; Sarah Rafika; Enty Enty; Lucky H. Moehario (Indonesian Pediatric Society, 2011)
AbstractBackground Vascular access may increase the risk of bloodstream infections, especially in newborn infants with weak immune systems and requiring invasive supportive care. Skin disinfection prior to peripheral venous catheter insertion lowers the risk of infection. However, antiseptics chosen for this task should be effective and safe for newborn infants.Objective To compare the effectiveness of 70% alcohol (BD alcohol swabs ®), 10% povidone-iodine (Pharma-RSUPNCM), and octenidine (Octenisept ®) as antiseptics for reducing skin bacteria for pre-invasive procedures in neonates.Methods Infants aged less than 28 days, regardless of gestational age, at the Neonatal Unit of Cipto Mangunkusumo Hospital (RSUPNCM) were included in our study. Infants were divided into three groups, each tested with different skin antiseptics (alcohol, povidone-iodine or octenidine). Skin swabs were performed before and after application of skin antiseptic, followed by inoculation onto blood agar plates. Colony-forming units were counted after 18 hours of incubation at 37ºC.Results Ninety subjects were divided into 3 groups of 30, each group using either 70% alcohol swabs, 10% povidone-iodine, or octenidine as skin antiseptic. Skin swabs were taken before and after antiseptic application and drying, as well as 5 minutes after application. The mean reductions in CFU/cm2 (%) after antiseptic application (and fully dried) were 97.54% for povidone-iodine, 97.52% for octenidine, and 89.07% for alcohol. There were no significant differences in mean CFU reductions among the three antiseptics groups (P=0.299). Furthermore, 5 minutes after application, there were still no significant differences in the three antiseptic groups (P=0.289).Conclusions Although octenidine showed a significant bacterial count reduction after application, it was not significantly different from those of alcohol or povidone-iodine. [Paediatr Indones. 2011;51:277-81].